Pirates of the Caribbean At world's end - Elliott, Ted 1961-; Rossio, Terry; Verbinski, Gore; Jerry Bruckheimer Films (Burbank, Calif Walt Disney Home Entertainment Distributed by Buena Vista Home Entertainment, 2007)
After Elizabeth, Will, and Captain Barbossa rescue Captain Jack Sparrow, who is trapped in Davy Jones' Locker, they must face their foes. Lord Cutler Beckett, now has control of Jones' heart and forms a dark alliance with him in order to rule the seas and wipe out the last of the Pirates. Jack, Barbossa, Will, Elizabeth, and crew must call the Pirate Lords from the four corners of the globe, including the infamous Sao Feng, together. The Pirate Lords want to release the goddess Calypso, Davy Jones's damned lover, from the trap they sent her. The Pirate Lords must combine the 9 pieces that bound her by ritual to undo it and release her in hopes that she will help them fight. All pirates will stand together and make their final stand for freedom against Beckett, Jones, Norrington, the Flying Dutchman, and the entire East India Trading Company
Based on the characters created by Ted Elliott & Terry Rossio and Stuart Beattie and Jay Wolpert ; Based on Walt Disney's "Pirates of the Caribbean" ride
1
Keywords: Pirates -- Caribbean Area -- Drama; Pirates -- Pacific Ocean -- Drama; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs